2020
DOI: 10.1155/2020/4103264
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Polymorphisms in TNFRSF11 with the Progression of Genetic Susceptibility to Gastric Cancer

Abstract: Objective. To investigate the relationship between polymorphism of TNFRSF11 gene rs9533156 and rs2277438 and susceptibility to gastric cancer. Methods. A case-control study was conducted to select 577 cases of primary gastric cancer and 678 cases of normal control. We extracted whole blood genomic DNA and amplified the target gene fragment by PCR. The genotyping and allele were tested through the snapshot method. Results. In this case-control study, we observed that there was a difference in the genotype distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Previous studies have shown that risk of GC is higher in smokers and drinkers when compared to nosmokers and no-drinkers [19][20][21][22][23]. However, studies have also found that non-drinkers [24] and non-smokers are still at the risk of developing GC [4]. Our results manifested that there was a correlation between the lifestyle of non-smokers and non-drinkers and the risk of GC.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Previous studies have shown that risk of GC is higher in smokers and drinkers when compared to nosmokers and no-drinkers [19][20][21][22][23]. However, studies have also found that non-drinkers [24] and non-smokers are still at the risk of developing GC [4]. Our results manifested that there was a correlation between the lifestyle of non-smokers and non-drinkers and the risk of GC.…”
Section: Discussionsupporting
confidence: 57%
“…In recent years, the study of SNP has become an effective tool and method for molecular genetics research, and has attracted much attention [16]. In our study, three SNPs (rs2297810, rs4646491 and rs2297809) of the CYP4B1 gene were taken as the research objects to explore the relationship between them and GC risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNFRSF11 (RANK) was rst found to have a role in bone dissolution and lymph node formation, majorly via the RANK/RANKL/OPG pathway [52]. current studies have proved the critical role of RANK/RANKL/OPG in cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%